Fuzzy classification based identification of voltage sag via wavelets - Mukerjee R.N.; Tanggawelu B.; Rogers G.J.; Soyat S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Increasing awareness of power quality issues, deregulation, use of consumer devices sensitive to power system disturbance and possibility of making up some of the inherent design limitations through monitoring based operational strategies have created a need for extensive monitoring of the power system operation. Voltage disturbance is a common phenomenon in electric power distribution system operation. A fuzzy diagnostic procedure is proposed for detecting cause of voltage disturbance, so that appropriate remedial procedures could be initiated during system operation. The method uses indices like PN factor, characteristic voltage, and zero sequence voltage and also proposes an index termed frequency jump index, extracted from zero sequence voltage using wavelets. 2002 Nanyang Technological University.